Semi-selective culture medium for Exserohilum turcicum isolation from corn seeds - De Rossi, Roberto Luis (2014)
Northern corn leaf blight, caused by Exserohilum turcicum (Et), is a disease of widespread occurrence in regions where corn, sweetcorn and popcorn are grown. This disease has great potential to cause damage and has been studied for years, but the association of its causal agent with seeds remains unconfirmed. Thus, the availability of a sensitive method to detect and quantify the inoculum in seeds, even at low incidence, is essential. The aim of this study was to develop a method to detect and quantify the presence of the fungus infecting and infesting corn and popcorn seeds. Artificially and naturally infected seeds were employed to develop the medium. The semi-selective medium was composed of carbendazim (active ingredient) (60 mg/L), captan (30 mg/L), streptomycin sulfate (500 mg/L) and neomycin sulfate (600 mg/L) aggregated to the medium lactose casein hydrolysate agar medium. By using this, Et was detected in naturally infected corn seeds, showing 0.124% incidence, in four out of ten analyzed samples. In addition, 1.04 conidia were detected per infested seed. By means of isolation, pathogenicity test, morphological characterization and comparison with descriptions of the species in the literature, the fungus isolated from the seeds was confirmed to be Et. Both infection and infestation were considered low; thus, for studies of Et detection in corn seeds, the use of semi-selective medium and more than 1,200 seeds/sample is suggested.